2012
DOI: 10.1123/tsp.26.3.435
|View full text |Cite
|
Sign up to set email alerts
|

How Do Coaches Experience Psychological Momentum? A Qualitative Study of Female Elite Handball Teams

Abstract: Psychological Momentum (PM) is commonly referred to in competitive sports, but still has to be considered elusive from a scientific perspective. This study explores coaches’ perception of triggers, strategies and characteristics of PM in female elite handball teams. Semi-structured interviews with nine coaches were evaluated using a qualitative content analysis. The results revealed that positive and negative PM were characterized by factors regarding behavior, cognition, confidence, emotions, and the team. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 45 publications
1
46
2
2
Order By: Relevance
“…The results of these analyses were non-significant, thus revealing that the display of nonverbal post-shot celebrations after scoring cannot be considered as a sufficient intervention to enhance subsequent performance. This result is in contrast to qualitative research: Handball players (Ronglan, 2007) respectively coaches (Moesch & Apitzsch, 2012) considered celebration behaviour to have a positive impact on performance. This belief, however, cannot be supported with the data of the present study.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…The results of these analyses were non-significant, thus revealing that the display of nonverbal post-shot celebrations after scoring cannot be considered as a sufficient intervention to enhance subsequent performance. This result is in contrast to qualitative research: Handball players (Ronglan, 2007) respectively coaches (Moesch & Apitzsch, 2012) considered celebration behaviour to have a positive impact on performance. This belief, however, cannot be supported with the data of the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…In line with previous conceptualizations of PM (e.g., Vallerand, Colavecchio, & Pelletier, 1988), these authors thus suggested that both individual and situational factors made up a complex interaction to create perceptions of PM. Affective responses have emerged as an important factor in PM from both qualitative and quantitative research (e.g., Briki, Den Hartigh, Bakker, & Gernigon, 2012;Briki, Den Hartigh, Hauw, & Gernigon, 2012;Cornelius, Silva, Conroy, & Petersen, 1997;Jones & Harwood, 2008;Moesch & Apitzsch, 2012). The expression of such affective responses through nonverbal behaviours has also been in focus in PM research: Moesch and Apitzsch (2012) revealed that handball coaches considered showing positive reactions within a team as a useful strategy to enhance positive PM, while negative body language is considered a trigger of negative PM.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that perceptions of PM exist and alter in response to gaining or losing ground in a competition (i.e., scoring or conceding) (Briki, Den Hartigh, Hauw, & Gernigon, 2012;Eisler & Spink, 1998;Iso-Ahola & Dotson, 2014;Moesch & Apitzsch, 2012;Perreault et al, 1998;Stanimirovic & Hanrahan, 2004) and therefore might be a possible explanation why a player's performance changes in relation to the score line. Therefore, in this paper the definition of PM as a "perception that the actor is progressing towards his/her goal" (Vallerand et al, 1988, p. 94) will be used, as it considers the perception of the performer as well as the act of scoring which has been shown to be a key determinant of PM in soccer (Higham, Harwood, & Cale, 2005;Jones & Harwood, 2008).…”
Section: Introductionmentioning
confidence: 99%